2014
DOI: 10.1002/pi.4712
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing polymer-based bulk heterojunction solar cells via crosslinking

Abstract: cited By 42International audienceReviewed are crosslinking strategies to stabilize the active-layer morphology of organic solar cells, namely donor-to-donor, donor-to-acceptor and acceptor-to-acceptor. The active layer of a polymer photovoltaic cell is mainly based on a blend of two components: a semiconducting polymer (electron donor) and a fullerene derivative (electron acceptor) to form the bulk heterojunction (BHJ). To offer optimum photovoltaic performances, the morphology of this layer has to be very car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 60 publications
0
77
0
Order By: Relevance
“…Several techniques have been developed over the last decade to improve the thermal stability of polymer:fullerene blends including the use of high glass transition temperature polymers, [14] ternary blends with compatibilizers such as block copolymers, [15][16][17] amorphous fullerene derivatives, [18,19] donor-acceptor systems with enhanced interactions, [20,21] functionalized side chains on the polymer, [22] thermocleavable polymers, [23] light-induced fullerene polymerization, [24,25] and cross-linkable materials. [26,27] Furthermore, it was shown that mixtures of different fullerenes can improve the thermal stability of BHJs. [28][29][30][31][32] Despite an intense research, known techniques to stabilize BHJs either reduce only partially thermal degradation or produce poor device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been developed over the last decade to improve the thermal stability of polymer:fullerene blends including the use of high glass transition temperature polymers, [14] ternary blends with compatibilizers such as block copolymers, [15][16][17] amorphous fullerene derivatives, [18,19] donor-acceptor systems with enhanced interactions, [20,21] functionalized side chains on the polymer, [22] thermocleavable polymers, [23] light-induced fullerene polymerization, [24,25] and cross-linkable materials. [26,27] Furthermore, it was shown that mixtures of different fullerenes can improve the thermal stability of BHJs. [28][29][30][31][32] Despite an intense research, known techniques to stabilize BHJs either reduce only partially thermal degradation or produce poor device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the crosslinking of donor polymers, crosslinkable fullerene derivatives were also investigated in the last years and are discussed in the reviews of Wantz et al and Rumer et al [14] …”
Section: Overview Of the Chemistry Of Crosslinkable Materialsmentioning
confidence: 99%
“…This is among the highest PCEs reported for OPVs using crosslinked active layers. [34] In the context of oxetane functionalization, it is noteworthy that, although it is generally assumed that this mechanism requires the exposure to an acid, [14,35] Knauer et al [15] showed that crosslinking via oxetane groups can be achieved by prolonged heating, yielding a fully crosslinked and long-term stable BHJ cell.…”
Section: Application Of Crosslinking In Organic Photovoltaicsmentioning
confidence: 99%
See 2 more Smart Citations